Transition metal sulfide heterojunction electro-catalytic material prepared by sequential vulcanization method and application of transition metal sulfide heterojunction electro-catalytic material
The carbon nanosheet-modified nitrogen and sulfur-coated transition metal sulfide heterojunction Co4S3-Co9S8@CNSs//CM was prepared by sequential vulcanization method, which solved the problem of poor stability of the catalyst in different electrolytes and achieved more efficient electrolytic catalytic performance and stability.
Patent Information
- Application Number
- CN202411827071.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-14
AI Technical Summary
The existing transition metal sulfide catalysts are poorly stable, are prone to corrosion and agglomerated among different electrolytes, limiting their application in the industrial field.
The carbon nanosheet-modified nitrogen and sulfur-coated transition metal sulfide heterojunction Co4S3-Co9S8@CNSs//CM was prepared by sequential vulcanization method. Through the metal organic frame as the precursor, a catalyst with a composite multi-stage structure was formed by using multi-step calcination and vulcanization processes at different temperatures.
The electrolytic water catalytic performance of the catalyst is improved, its stability and erosion resistance in all pH electrolytic water is enhanced, and more active sites and larger electrochemical catalytic specific surface area are provided.
Smart Images

Figure CN119615260A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of nanomaterial synthesis and electrochemical technology, and specifically prepares carbon nanosheet-modified nitrogen and sulfur co-doped carbon matrix-coated transition metal sulfide-type matrix Co4S3-Co9S8@CNSs / / CM by a sequential sulfurization method. Background Art
[0002] Since the Industrial Revolution, with the rapid development of modern science and technology, the consumption rate and demand of various energy sources and fossil fuels (coal, oil, natural gas) have also increased sharply. Secondly, with the large-scale use of fossil fuels in recent years, a large amount of toxic and harmful gases have been discharged into the atmosphere, which has also induced a series of problems such as greenhouse effect and environmental pollution. The rapid development of people has been seriously restricted by energy problems, and traditional energy is far from meeting the needs of current social development. Therefore, the development of new, pollution-free new energy is imminent. The development of new energy has become the key to alleviating environmental pollution and energy depletion problems, and it is also a global research hotspot. Based on this, the research and development of efficient, clean and pollution-free energy mining technology, conversion technology and storage technology has received strong support from the country and the government. Hydrogen energy, due to its high combustion calorific value, clean and pollution-free, and no carbon emission, has rapidly entered the public's field of vision in recent years, attracting widespread attention from many people in society, and is expected to replace traditional fossil fuels. Among them, hydrogen production from fossil fuels is the most widely used method of hydrogen production. Although its technology is mature and its output is large, it still has a strong dependence on fossil fuels, which goes against our original intention of developing new energy sources. In addition, this method of hydrogen production also faces problems such as environmental pollution and resource depletion. Hydrogen production from water electrolysis effectively solves the drawbacks of burning fossil fuels from both the resource and environmental aspects, and completely achieves "zero emissions" of greenhouse gases. Thereby truly meeting the requirements of a sustainable development strategy. As the core of hydrogen production from water electrolysis, the catalyst plays an important role in reducing the reaction overpotential and accelerating the reaction kinetics during the water electrolysis process. It effectively improves the energy conversion efficiency in this link and lays a solid foundation for the development of hydrogen production from water electrolysis technology.
[0003] Recent studies have found that transition metal sulfide (TMS) is a promising hydrogen evolution reaction (HER) catalyst. Transition metal sulfide can greatly increase the efficiency of charge transfer due to its unique electronic structure, and its activity (catalytic performance) in water electrolysis can even surpass that of precious metal catalysts to a certain extent. However, TMS has poor stability in different electrolytes (strong acid, strong base), is susceptible to corrosion, and is easy to agglomerate, which limits its further application in the industrial field. However, the emergence of metal organic frameworks (MOFs) provides a good idea for solving this problem. Because of its large specific surface area, pore diversity and structural adjustability, nanomaterials prepared with it as a precursor have many applications in the field of electrocatalysis. Therefore, the present invention is to prepare a transition metal sulfide catalyst using nanomaterials derived from metal organic frameworks as precursors. The synthesized product has a unique multi-level structure, provides multi-dimensional mass / charge transfer channels and more abundant active sites in the electrolysis of water at all pH levels, and can better ensure that the heterogeneous structure coated inside it is protected from the erosion of the electrolyte.
[0004] Therefore, designing and developing synthesis strategies for transition metal sulfide catalysts with the goal of effectively improving their catalytic performance in water electrolysis is a challenging research topic in this field. Summary of the invention
[0005] The present invention provides a transition metal sulfide heterojunction Co4S3-Co9S8@CNSs / / CM coated with nitrogen and sulfur co-doped carbon matrix modified by carbon nanosheets prepared by sequential sulfurization method, which solves the current problems of synthesis and electronic structure regulation of such materials.
[0006] The present invention is achieved through the following technical solutions:
[0007] A transition metal sulfide heterojunction electrocatalytic material, whose general molecular formula is Co4S3-Co9S8@CNSs / / CM.
[0008] A method for preparing the aforementioned transition metal sulfide electrocatalytic material comprises the following steps:
[0009] S1, preparing a cobalt-based metal organic framework by stirring a room temperature solution, denoted as ZIF-67;
[0010] S2, the prepared ZIF-67 and commercial sulfur powder were heated in a programmed temperature manner for annealing, and then cooled naturally to obtain nitrogen and sulfur co-doped matrix-coated Co4S3 nanocubes, denoted as Co4S3@CM;
[0011] S3. The Co4S3@CM and sulfur powder are further high-temperature sulfurized at 650-750°C for 2h to prepare Co4S3-Co9S8 heterostructure nanoparticles coated with a nitrogen and sulfur co-doped matrix modified by carbon nanosheets, which are recorded as Co4S3-Co9S8@CNSs / / CM.
[0012] As a preferred embodiment, the preparation method of the cobalt-based metal organic framework is:
[0013] Cobalt nitrate hexahydrate is used as a metal ion donor, 2-methylimidazole is used as an organic ligand, and hexadecyltrimethylammonium bromide is used as a surfactant. The three are mixed and put into deionized water and dispersed evenly. Stirring is performed at room temperature for 3 hours (20-30°C), followed by centrifugal washing to obtain a cubic precursor ZIF-67.
[0014] Subsequently, during the vulcanization process, samples with different properties were synthesized according to different heating temperatures.
[0015] As a preferred solution, the weight ratio of ZIF-67 to sulfur powder is 2:1
[0016] The first sulfurization was carried out with a weight ratio of ZIF-67 to sulfur powder of 2:1. In an argon atmosphere, it was heated to 600 °C and kept for 2 h. After cooling to room temperature, the nitrogen- and sulfur-coated matrix-coated nanocube Co4S3@CM was obtained.
[0017] As a preferred solution, the weight ratio of Co4S3@CM to sulfur powder is 1:2
[0018] The weight ratio of Co4S3@CM to sulfur powder was 1:2 for the second sulfurization. Under argon atmosphere, the temperature was raised to 700 °C at the same heating rate for secondary sulfurization and kept for 2 h. After natural cooling, the heterostructured nanoparticles of Co4S3-Co9S8 coated with nitrogen and sulfur co-doped matrix modified by carbon nanosheets were obtained, which were recorded as Co4S3-Co9S8@CNSs / / CM.
[0019] Then, Co4S3@CM and sulfur powder were sulfurized at 600℃ and 900℃ in the same mass ratio to obtain electrochemical performance test comparison samples.
[0020] As a preferred embodiment, the heating rate of the programmed temperature increase is 1 to 5°C / min.
[0021] A transition metal sulfide heterojunction electrocatalytic material obtained by the above-mentioned preparation method.
[0022] A use of the aforementioned transition metal sulfide heterojunction electrocatalytic material in an electrocatalytic hydrogen evolution reaction.
[0023] The reaction mechanism of the present invention is:
[0024] The correct synthesis strategy is the key to improving the performance of non-precious metal catalysts for hydrogen evolution in water electrolysis. The present invention takes advantage of the large specific surface area, diverse pores and structural adjustability of metal organic framework materials, adopts a sequential sulfurization strategy, performs multi-step calcination at different temperatures, and successfully synthesizes a heterojunction catalyst Co4S3-Co9S8@CNSs / / CM coated with a nitrogen and sulfur co-doped matrix modified with carbon nanosheets.
[0025] Compared with the prior art, the advantages and positive effects of the present invention are:
[0026] The present invention utilizes a sequential sulfurization strategy to allow the precursor to produce a composite multi-level structure during the calcination process. The synthesized heterojunction catalyst Co4S3-Co9S8@CNSs / / CM has a carbon nanosheet and nanoparticle and nanocube doped morphology. This unique morphology has more abundant active sites and a larger electrochemical catalytic specific surface area, which can effectively improve the catalytic performance of the material. At the same time, the unique carbon skeleton structure ensures that the heterostructure coated inside Co4S3-Co9S8@CNSs / / CM is protected from erosion by the electrolyte and can be used in a wider range of solution conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0028] Figure 1 This is a SEM image of ZIF-67 prepared in Example 1 of the present invention;
[0029] Figure 2 It is the BET diagram of ZIF-67 prepared in Example 1 of the present invention;
[0030] Figure 3 This is a SEM image of the transition metal sulfide heterojunction Co4S3-Co9S8@CNSs / / CM electrocatalytic material prepared in Example 2 of the present invention;
[0031] Figure 4 This is the BET diagram of the transition metal sulfide heterojunction Co4S3-Co9S8@CNSs / / CM electrocatalytic material prepared in Example 2 of the present invention;
[0032] Figure 5 This is the XRD pattern of the transition metal sulfide heterojunction Co4S3-Co9S8@CNSs / / CM electrocatalytic material prepared in Example 2 of the present invention;
[0033] Figure 6 TEM image of the transition metal sulfide heterojunction Co4S3-Co9S8@CNSs / / CM electrocatalytic material prepared in Example 2 of the present invention;
[0034] Figure 7 HRTEM image of the transition metal sulfide heterojunction Co4S3-Co9S8@CNSs / / CM electrocatalytic material prepared in Example 2 of the present invention;
[0035] Figure 8 The linear sweep voltammogram obtained by testing the electrocatalytic material prepared in Example 2 in 0.5M H2SO4 electrolyte;
[0036] Fig. 9 is a Tafel slope graph of the electrocatalytic material prepared in Example 2 tested in a 0.5M H2SO4 electrolyte;
[0037] Fig.10 This is a stability test graph of the electrocatalytic material prepared in Example 2 tested in a 0.5M H2SO4 electrolyte;
[0038] Fig.11 This is a linear sweep voltammogram of the electrocatalytic material prepared in Example 2 tested in 1M KOH electrolyte;
[0039] Fig.12 is a Tafel slope graph of the electrocatalytic material prepared in Example 2 tested in 1M KOH electrolyte;
[0040] Fig.13 This is a stability test graph of the electrocatalytic material prepared in Example 2 tested in 1M KOH electrolyte;
[0041] Fig.14 is a linear sweep voltammogram of the electrocatalytic material prepared in Example 2 tested in 1M PBS electrolyte;
[0042] Fig.15 is a Tafel slope graph of the electrocatalytic material prepared in Example 2 tested in 1M PBS electrolyte;
[0043] Fig.16 This is a stability test chart of the electrocatalytic material prepared in Example 2 tested in 1M PBS electrolyte. DETAILED DESCRIPTION
[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Embodiment 1:
[0046] This embodiment provides a method for preparing Co4S3-Co9S8@CNSs / / CM nanohybrid, which specifically comprises the following steps:
[0047] (1) Preparation of ZIF-67 and comparative sample precursors: 1.0 mmol of cobalt nitrate hexahydrate and 15 mg of hexadecyltrimethylammonium bromide were dissolved in 30 ml of deionized water. Subsequently, the mixed solution was poured into deionized water containing 13.62 g of 2-methylimidazole, and the mixture was further stirred for 3 hours until it was completely dissolved at room temperature. Then, a large amount of methanol was used for centrifugation to obtain a cubic precursor, which was recorded as ZIF-67.
[0048] (2) Preparation of Co4S3-Co9S8@CNSs / / CM nanohybrid: 40 mg of ZIF-67 was placed on one side of a quartz boat and evenly spread. 20 mg of sulfur powder was placed on the other side of the quartz boat and stacked. The quartz boat was transferred to a tube furnace, with the side where the sulfur powder was stacked aligned with the inlet of the tube furnace. The heating rate was 5 °C / min, and the mixture was heated to 600 °C in an argon atmosphere and kept warm for 2 h. After cooling to room temperature, a black product was obtained, named Co4S3@CM. Subsequently, Co4S3@CM and sulfur powder were subjected to secondary sulfurization in a mass ratio of 1:2 according to the above scheme. In an argon atmosphere, the mixture was sulfurized at an annealing temperature of 700 °C for 2 h and cooled to room temperature to obtain Co4S3-Co9S8@CNSs / / CM coated with a nitrogen and sulfur co-doped matrix modified by carbon nanosheets. Next, Co4S3@CM and sulfur powder were sulfurized at the same mass ratio at 600°C and 900°C in an argon atmosphere to obtain Co4S3@CM and Co9S8@CM for subsequent comparative testing.
[0049] (3) Electrochemical performance test of Co4S3-Co9S8@CNSs / / CM, Co4S3@CM and Co9S8@CM in different electrolytes: 5 mg of the prepared sample was placed in a 2 mL centrifuge tube, and then 1 mL of deionized water, 950 μL of ethanol and 50 μL of Nafion were added, and ultrasonic treatment was performed for 30 min to obtain a uniform solution. Then 5 μL of the solution was dropped on the polished glassy carbon electrode, dried at room temperature, and then placed in 0.5 M H2SO4, 1.0 M KOH and 1.0 M PBS for electrochemical hydrogen production performance evaluation.
[0050] Figure 1 The SEM image of ZIF-67 prepared in Example 1 shows that the ZIF-67 precursor prepared by us has a relatively regular nanocube appearance with an average diameter of about 400 nm.
[0051] Figure 2BET image of ZIF-67 prepared in Example 1 under nitrogen atmosphere. The curve of precursor ZIF-67 is a type I isotherm, and its BET value is 1346.6 m 2 ·g -1 This also means that the obtained ZIF-67 has a suitable pore size and can introduce heteroatoms and other guest molecules through sulfurization and other methods, while the larger specific surface area can provide more active sites for the subsequent synthesis of catalytic materials.
[0052] Example 2
[0053] This embodiment provides a transition metal sulfide heterojunction The preparation method of Co4S3-Co9S8@CNSs / / CM electrocatalytic material specifically comprises the following steps:
[0054] Take 40 mg of ZIF-67 and place it evenly on one side of the quartz boat, then take 20 mg of sulfur powder and place it on the other side of the quartz boat, transfer the quartz boat to the tube furnace, keep the side where the sulfur powder is piled consistent with the air inlet of the tube furnace, heat it at a rate of 5 ° C / min, heat it to 600 ° C in an argon atmosphere and keep it warm for 2 hours. After cooling to room temperature, a black intermediate product is obtained, named Co4S3@CM. Subsequently, Co4S3@CM and sulfur powder are used in a mass ratio of 1:2, and secondary sulfurization is performed according to the above scheme. Under an argon atmosphere, the annealing temperature is sulfurized at 700 ° C for 2 hours, and then cooled to room temperature to obtain Co4S3-Co9S8@CNSs / / CM coated with a nitrogen and sulfur co-doped matrix modified by carbon nanosheets. Next, Co4S3@CM and sulfur powder are sulfurized at the same mass ratio at 600 ° C and 900 ° C in an argon atmosphere to obtain Co4S3@CM and Co9S8@CM.
[0055] Figure 3 This is a SEM image of the transition metal sulfide heterojunction Co4S3-Co9S8@CNSs / / CM electrocatalytic material prepared in Example 2. After ZIF-67 is further sulfurized to obtain a heterostructured nanomaterial, not only nanospheres but also some nanosheets are generated on the surface of the material. The presence of these nanospheres / nanosheets provides the possibility of further improving the catalytic activity of this heterostructured catalyst.
[0056] Figure 4 This is the BET graph of Co4S3-Co9S8@CNSs / / CM prepared in Example 2. It can be seen from the figure that the nitrogen adsorption-desorption isotherm of Co4S3-Co9S8@CNSs / / CM is similar to that of ZIF-67, but the BET surface area is reduced to 96.4 m 2 / g. This indicates that the sulfur source was successfully encapsulated into the pore structure inside the MOF during the subsequent sulfurization stage.
[0057] Figure 5 This is the XRD pattern of the transition metal sulfide heterojunction Co4S3-Co9S8@CNSs / / CM electrocatalytic material prepared in Example 2. By comparing the XRD pattern of Co4S3-Co9S8@CNSs / / CM with the JCPDS standard spectrum, it can be observed that Co4S3 and Co9S8 coexist. Through the analysis of the results, it can be concluded that the Co4S3 / Co9S8 heterojunction has been successfully embedded in the carbon matrix.
[0058] Figure 6 This is a TEM image of the transition metal sulfide heterojunction Co4S3-Co9S8@CNSs / / CM electrocatalyst material prepared in Example 2. The nanocatalyst still maintains a complete cubic morphology, and the surrounding carbon nanospheres and carbon nanosheets are also clearly visible.
[0059] Figure 7 This is a HRTEM image of the transition metal sulfide heterojunction Co4S3-Co9S8@CNSs / / CM electrocatalytic material prepared in Example 2. The high-resolution (HRTEM) image highlights two different lattice spacings, where the lattice spacings of 0.28 nm and 0.198 nm correspond to the (440) plane of Co4S3 and the (511) plane of Co9S8, respectively.
[0060] Example 3
[0061] In the conventional three-electrode experimental setup, a graphite rod was selected as the auxiliary electrode, an Ag / AgCl electrode containing saturated KCl was selected as the reference electrode, and a glassy carbon electrode was used as the working electrode. 5.0 mg of the prepared sample was dispersed in a mixed solution of 0.5 mL of Nafion (5% (w / w)), deionized water, and ethanol solution (volume ratio of 1:9:10), and a uniform solution was formed with the help of ultrasound. Then 5 μL of the solution was dripped on a glassy carbon electrode with a diameter of 3 mm. The electrode was allowed to dry naturally at room temperature for two hours, and then the measurement was performed (loading amount: 0.35 mg cm -2 )
[0062] Figure 8 The linear sweep voltammogram of the electrocatalytic material prepared in Example 2 and commercial Pt / C in 0.5M H2SO4 electrolyte was tested. The electrocatalytic performance of the three prepared materials Co4S3-Co9S8@CNSs / / CM, Co4S3@CM and Co9S8@CM was verified. Among them, Co4S3-Co9S8@CNSs / / CM showed the highest activity, corresponding to 10mA cm -2 At a current density of 1.34 W, its overpotential is 190 mV, and its performance is closest to that of commercial Pt / C materials.
[0063] Fig. 9This is the Tafel slope graph of the electrocatalytic material prepared in Example 2 and commercial Pt / C tested in 0.5M H2SO4 electrolyte. Among the three prepared materials, Co4S3-Co9S8@CNSs / / CM exhibits the fastest reaction kinetics, close to the performance of commercial Pt / C materials, with a Tafel slope of 120mV·dec -1 It also shows that H2 desorption is a rate-determining step in the hydrogen evolution reaction of Co4S3-Co9S8@CNSs / / CM, following the Volmer-Heyrovsky pathway.
[0064] Fig.10 This is a stability test diagram of the electrocatalytic material prepared in Example 2 tested in 0.5M H2SO4 electrolyte. Under the long-term chronoamperometric test, the current density of Co4S3-Co9S8@CNSs / / CM still remained at 98.4% of the initial current density, proving that it has good stability in acidic media.
[0065] Fig.11 This is the linear sweep voltammogram obtained by testing the electrocatalytic material prepared in Example 2 and commercial Pt / C in 1M KOH electrolyte. In the 1M KOH electrolyte environment, Co4S3-Co9S8@CNSs / / CM still has a low overpotential (224mV)
[0066] Fig.12 This is the Tafel slope graph of the electrocatalytic material prepared in Example 2 and commercial Pt / C tested in 1M KOH electrolyte. The Tafel slope of Co4S3-Co9S8@CNSs / / CM in 1M KOH electrolyte is 132mV·dec -1 .
[0067] Fig.13 This is a stability test chart of the electrocatalytic material prepared in Example 2 tested in 1M KOH electrolyte. Under the same long-term chronoamperometric test, the current density of Co4S3-Co9S8@CNSs / / CM still remained at 94.3% of the initial current density, indicating that Co4S3-Co9S8@CNSs / / CM still has the ability to work for a long time in alkaline media.
[0068] Fig.14 The linear sweep voltammogram of the electrocatalytic material prepared in Example 2 and commercial Pt / C in 1M PBS electrolyte. In 1M PBS electrolyte environment, Co4S3-Co9S8@CNSs / / CM still has a low overpotential (264mV)
[0069] Fig.15This is the Tafel slope graph of the electrocatalytic material prepared in Example 2 and commercial Pt / C in 1M PBS electrolyte. The Tafel slope of Co4S3-Co9S8@CNSs / / CM in 1M PBS electrolyte is 159.6 mV·dec -1 .
[0070] Fig.16 This is a stability test chart of the electrocatalytic material prepared in Example 2 and commercial Pt / C in 1M PBS electrolyte. Under the same long-term chronoamperometric test, the current density of Co4S3-Co9S8@CNSs / / CM still remains at 88.3% of the initial current density, indicating that Co4S3-Co9S8@CNSs / / CM still has good stability in neutral media.
[0071] The present invention is not limited to the specific details of the above exemplary embodiments. Without violating the core spirit and basic features of the present invention, the present invention can be implemented in different specific forms. Therefore, no matter from which aspect, the embodiments should be regarded as illustrative rather than restrictive. The scope of protection of the present invention is defined by the attached claims, not the above description. This means that all changes within the meaning and scope of the equivalent elements of the claims should be regarded as part of the present invention. Any figure mark in the claims should not be understood as a limitation of the claims.
Claims
1. A process for preparing transition metal sulfide heterojunction electrocatalytic materials by sequential sulfurization, characterized in that: The steps include: S1. A cubic cobalt-based metal organic framework was prepared by stirring a room temperature solution, which was denoted as ZIF-67; S2, the prepared ZIF-67 and commercial sulfur powder were heated in a programmed temperature manner for annealing, and then cooled naturally to obtain nitrogen and sulfur co-doped matrix-coated Co4S3 nanocubes, denoted as Co4S3@CM; S3. The Co4S3@CM and sulfur powder are further high-temperature sulfurized at 650-750°C for 2h to prepare a Co4S3-Co9S8 heterojunction coated with a nitrogen and sulfur co-doped matrix modified by carbon nanosheets, which is recorded as Co4S3-Co9S8@CNSs / / CM. The transition metal sulfide heterojunction electrocatalytic material is characterized by having a multi-level structure doped with nanosheets and nanocubes.
2. The method for preparing a transition metal sulfide heterojunction electrocatalytic material according to claim 1, characterized in that: The preparation method of the cobalt-based metal organic framework is as follows: Cobalt nitrate hexahydrate is used as a metal ion donor, 2-methylimidazole is used as an organic ligand, and hexadecyltrimethylammonium bromide is used as a surfactant. The three are mixed and put into deionized water and dispersed evenly. Stirring is performed at room temperature for 3 hours (20-30°C), followed by centrifugal washing to obtain a cubic precursor ZIF-67.
3. The transition metal sulfide heterojunction sequential sulfurization method according to claim 1, characterized in that: The weight ratio of ZIF-67 to commercial sulfur powder in the first vulcanization is 2:1, and the weight ratio of Co4S3@CM to commercial sulfur powder in the second vulcanization is 1:
2. The annealing method is that the first vulcanization is heated to 600°C, kept for 2 hours, and naturally cooled to obtain Co4S3@CM; the second vulcanization is heated to 700°C, kept for 2 hours, and naturally cooled to obtain Co4S3-Co9S8@CNSs / / CM. The heating rate of the programmed temperature increase is 1 to 5°C / min.
4. A transition metal sulfide heterojunction electrocatalytic material obtained by the preparation method according to any one of claims 1 to 3.
5. Use of the transition metal sulfide heterojunction electrocatalytic material according to claim 1 in an electrocatalytic hydrogen evolution reaction.